Modernisation of Public Buildings in Polish Towns and the Concept of Sustainable Building - Chodkowska-Miszczuk, Justyna; Szymańska, Daniela (Quaestiones Geographicae, 2014)
This article aims to identify the scale of energy efficiency improvements in public buildings in Polish towns as representative of sustainable building. The study area is investigated from the perspective of challenges arising from the current policy in the EU. The article indicates that, given the age of public buildings in Poland, the best way to implement the concept of sustainable building is to improve their present stock. The modernisation of public buildings is discussed in terms of project location, project value, sources of funding (including EU funds), and the use of buildings undergoing modernisation. According to the research findings, the implementation of the sustainable building concept is determined by both, exogenous factors (EU directives and domestic laws, etc.) and endogenous ones (e.g. human resources and their quality)